World's greatest engineering icons [videorecording (DVD)] - Wilby, Sorrel; McAllum, Peter, 1946- (PBS, 2022)
The world is full of extraordinary buildings that soar and inspire; monumental marvels that have become cornerstones of our heritage and culture. The Great Pyramid of Giza, Angkor Wat, Stonehenge, The Acropolis, The Colosseum, Petra, The Forbidden City, Red Square, Buckingham Palace, The Eiffel Tower, Burj Khalifa, The Sydney Opera House, The White House, and more. Throughout six episodes we circle the globe, exploring the World's Greatest Icons: that honor the sacred, buildings that reach for the sky, fairytale castles, lavish royal palaces, built environments that enhance communities, and structures that represent power. Over fifteen unique buildings feature in every episode of World's Greatest Engineering Icons. Powerful imagery and narratives that closely follow the course of history allow us to explore the artistry, ingenuity, and engineering behind humanity's greatest architectural accomplishments: the structures that define who we are and all we aspire to achieve.